Cadmium, Chromium, and Lead Uptake Associated Health Risk Assessment of Alternanthera sessilis: A Commonly Consumed Green Leafy Vegetable - W. M. Dimuthu Nilmini Wijeyaratne; E. A. Charuni Sewwandi Kumari (Journal of Toxicology)
Green leafy vegetables are becoming increasingly popular in the developing countries due to their high nutritious value, common availability, and low cost. However, no studies have assessed the health risks associated with consumption of fresh green leafy vegetables. The present study assessed Cd, Cr, and Pb associated health risks in a commonly consumed green leafy vegetable in developing countries, Alternanthera sessilis. The Cd, Cr, and Pb concentrations in roots, leaves, and root zone soil of Alternanthera sessilis harvested from organic and non-organic cultivations were measured. The results indicated that Cd, Cr, and Pb concentrations in roots and leaves of Alternanthera sessilis exceeded the WHO/FAO safe limits for human consumption. Further, bioconcentration factor, soil to root, and root to leaf translocation factors indicated a potential of hyperaccumulating Cd in roots and leaves of Alternanthera sessilis. However, the target hazard quotients for Cd, Cr, and Pb were less than 1 indicating negligible health hazard associated with long time consumption of Alternanthera sessilis.